2014
DOI: 10.1111/jicd.12127
|View full text |Cite
|
Sign up to set email alerts
|

Changes in cellular and molecular components of peripheral blood in patients with generalized aggressive periodontitis

Abstract: The results showed possible changes in the cellular and molecular components of peripheral blood in patients with GAP compared to periodontally-healthy controls. These changes might represent the contribution of periodontal infections to systemic inflammation in relatively young individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 61 publications
1
10
1
Order By: Relevance
“…The previous study of this working group did not show remarkable differences regarding PCT (Ziebolz et al, ). Moreover, CRP and leucocytes were especially found to be increased in periodontitis subjects in previous examinations (Loos, ; Iqbal et al, ; Gaddale et al, ). Furthermore, a study by Anumolu et al .…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The previous study of this working group did not show remarkable differences regarding PCT (Ziebolz et al, ). Moreover, CRP and leucocytes were especially found to be increased in periodontitis subjects in previous examinations (Loos, ; Iqbal et al, ; Gaddale et al, ). Furthermore, a study by Anumolu et al .…”
Section: Discussionmentioning
confidence: 67%
“…Another question of the current study was the association of the periodontal disease severity with common blood parameters. Different previous investigations were able to present differences in blood parameters between periodontal healthy and diseased individuals (Fredriksson et al, ; Buhlin et al, ; Loos, ; Gomes‐Filho et al, ; Iqbal et al, ; Gaddale et al, ; Bolla et al, ). In the current study, only PCT showed conspicuous findings that were not confirmed in post‐hoc testing between the subgroups, which might suggest several statistical outliers.…”
Section: Discussionmentioning
confidence: 85%
“…Similar study in humans would not be ideal owing to the variability of samples, which could put the results into question. In addition, blood count is an extremely reliable test and has been used in several medical evaluations and scientific studies [13,18,19]. For those reasons, we found it prudent to use blood count in rats to confirm the hypothesis that infection of endodontic origin may influence systemic health.…”
Section: Discussionmentioning
confidence: 91%
“…The blood count is a highly reliable test and has been used for blood evaluation in several studies [13,18,19]. It is possible to evaluate several blood parameters such as the levels of erythrocytes, leukocytes, neutrophils, and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies (Pejcic et al, 2011;Gaddale et al, 2014) have confirmed an increased number of WBCs and neutrophils in the peripheral blood of patients with moderate to severe periodontitis, with a positive correlation between disease severity and number of WBCs in the blood.…”
Section: Discussionmentioning
confidence: 93%